Border Crossings, Pathfinders and New Visions: The Role of Sámi Literature in Contemporary Society - Kuokkanen, Rauna (Nordlit, 2004)
In this article, I will consider some of the current issues and concerns in contemporary Sámi literature. I view them as border crossings particularly because it seems that at least in certain ways, Sámi literature is on crossroads faced with some tough and serious issues. I suggest that we need to perceive Sámi writers as pathfinders who can, through their writing, guide us in considering what are the paths that the Sámi need to take today in order to have an active cultural connection in the future. Moreover, what is urgently needed in Sámi society is reclaiming Sámi values and vision for contemporary contexts in a meaningful way. In this process, Sámi writers have also a central role as they are the ones who constantly weave the past, present and future into a fabric that gives us the meanings we need to stay grounded in who we are.
Keywords: contemporary Sámi literature